How capitalism failed the Arab world : the economic roots and precarious future of Middle East uprisings - Heydarian, Richard Javad (Economic controversies., 2014)
Economic liberalization has failed in the Arab world. Instead of precipitating democratic reform, it has over the last three decades resulted in greater poverty, inequality and unemployment. In How Capitalism Failed the Arab World, Richard Javad Heydarian shows how years of economic mismanagement, political autocracy and corruption have encouraged people to revolt, and how the initial optimism of the uprisings is now giving way to bitter power struggles and continued economic stagnation.